Epidemiology and Risk Factors of Pelvic Inflammatory Disease. - Pandey, Bandana (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Knowledge of pelvic inflammatory disease and its epidemiology is essential to understand reproductive morbidity in women. This paper estimates the level of association between demographic factors and pelvic inflammatory disease in women in their reproductive age. Methods: A descriptive study done in Humla, Kritipur and Baudha by organizing a health camp. Women of reproductive age group and who have lower abdominal pain, pervaginal discharge, fever, and dysparunia were included in the study after taking informed verbal consent from the patient. Patients who have lower abdominal pain and pervaginal discharge were diagnosed as pelvic inflammatory disease. Results: Diagnoses of pelvic inflammatory disease were made in 30% of attendances amongst women aged between 16 to 48. Increased risk of pelvic inflammatory disease was associated with smoking (P<0.0001), age groups 31 – 40 yrs (44.6%),in rural areas(45%) and people who are illiterate (P<0.0001). Among 400, 383(95%) were reported ever using a modern contraceptive. Conclusion: The prevalence of pelvic inflammatory disease was 30% in reproductive age group and was significantly associated with smoking. doi: http://dx.doi.org/10.3126/mjsbh.v13i1.12992